The Texture of Everyday Life - Polić-Jurković, Vanja (Array, 2011)
The paper will explore some of the ways in which personal experience turns into life writing, the process in which a record of a life lived becomes a story, such as the textualization of the “texture” of life, or from body to book ; the emplotment of the incidences of life into a life narrative (White) ; the heteroglossia of life writing (Bakhtin) ; the finding of voice for one’s self (Eakin) ; and the role of memory in life writing (Olney). As specific backdrop to the discussion, the two well-known examples of Canadian literature, Susanna Moodie’s Roughing It in the Bush, and Margaret Atwood’s reinscription, The Journals of Susanna Moodie, will be used to exemplify some of the main arguments raised in the paper.